Retraction: [Quality Evaluation of Breakfast Cereal Meal Produced from Finger Millet (Eleusine coracana) and Roasted African Yam Beans (Sphenostylis stenocarpa) Flour Blends] - Owheruo, Joseph Oghenewogaga; Edo, Great Iruoghene; Bashir, Zubair Adeiza; Akpoghelie, Patrick Othuke; Agbo, Joy Johnson (Food Science and Engineering, 2023)
Retraction Note: Volume 7 Issue 1, FSE-9778 DOI: https://doi.org/10.37256/fse.7120269778 This study was carried out to evaluate the qualities of breakfast cereal meals produced from blends of finger millet and toasted African yam beans flour. Flour samples of processed finger millet were blended with roasted African yam beans flour at substitution levels of 0, 10, 20, 30, and 40%. The blended flours were processed into breakfast cereal. The breakfast cereal products were subjected to proximate, vitamin, mineral, and microbial analyses (mould count and total viable count) and sensory evaluation. The result showed that there was a significant increase in the protein, moisture, carbohydrate, and energy content of the breakfast cereals with a corresponding decrease in the ash and fiber content as the level of African yam bean flour increased in the blends. The proximate composition result of the breakfast cereal product ranged from 11.65-37.78% for protein, 13.70-4.91% for ash, 3.00-7.20% for fiber, 2.88-3.88% for moisture, 0.74-1.00% for fat, 46.41-76.77% for carbohydrate and 360.98-380.36% for energy. Vitamin composition of the products ranged from 43.17-72.14 UI for vitamin A, 0.058-0.184 mg/100 g for vitamin B1, 0.058-0.184 mg/100 g for vitamin B2, 0.006-0.015 mg/100 g for vitamin B3 0.289-0.516 mg/100 g. Mineral composition ranged from 6.50-10.01 mg/100 g for iron, 355.53-454.37 mg/100 g for calcium, and 27.65-28.75 mg/100 g for phosphorus content. The total viable count ranged from 2.7 × 102 to 2.8 × 102 cfu/g while the mould was not detected in any of the samples. Results of sensory evaluation showed that FAY60 was the most acceptable breakfast cereal meal.